2018
DOI: 10.3389/fpsyg.2018.00066
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Impact of Maximizing on Unhappiness: Two Competing Mediating Effects

Abstract: The current study aims to explore how the decision-making style of maximizing affects subjective well-being (SWB), which mainly focuses on the confirmation of the mediator role of regret and suppressing role of achievement motivation. A total of 402 Chinese undergraduate students participated in this study, in which they responded to the maximization, regret, and achievement motivation scales and SWB measures. Results suggested that maximizing significantly predicted SWB. Moreover, regret and achievement motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“…In particular, for individuals with a rational decision‐making style, cognitive ability can significantly predict decision‐making competence. For those with an intuitive decision‐making style, however, cognitive ability does not appear to significantly predict decision‐making competence (Del Missier et al, ; Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for individuals with a rational decision‐making style, cognitive ability can significantly predict decision‐making competence. For those with an intuitive decision‐making style, however, cognitive ability does not appear to significantly predict decision‐making competence (Del Missier et al, ; Peng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals make seemingly endless decisions in daily life, such as which brand of shampoo to use, what to wear, and whether to pursue conservative or risky treatment for a health condition. Most behavioral decision‐making research has focused on general rules of judgment and the discrepancy between actual decisions and an absolutely rational choice; individual differences have received comparatively little attention (Parker, De Bruin, & Fischhoff, ; Peng et al, ). However, the idea that individual differences in decision making are attributable to random error has long been contested.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Diab et al (2008) suggested that regret was a key variable in understanding the relationship between maximization and life satisfaction. Indeed, Peng et al (2018) found that regret served as a key mediator between maximization and subjective well-being. Kim and Miller (2017) found that when maximizers experience decision difficulty, they are more vulnerable to negative feedback about one's choice.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…They may continue this strategy of maximizing information‐gathering during the child’s infancy and early childhood as they maintain a vigil, collecting their information directly from observations of the child and comparisons to other children they assume are typical . Notably, such maximizing is associated with unhappiness …”
Section: How the Dilemma Of Action Impacts Pregnant Women And Their Pmentioning
confidence: 99%